Bone Tumors in the Young: Comparative Analysis of Osteosarcoma and Ewing Sarcoma in Pakistani Children - Shams, Amber; Lodi, Aisha; Rais, Aeman; Khan, Laiba Raheen; Haseeb, Furqan (Journal of Neonatal Surgery, 2025)
Background: Pediatric bone malignancies constitute a critical subset of childhood cancers, with osteosarcoma (OS) and Ewing sarcoma (ES) representing the two most common primary malignant bone tumors in children and adolescents. Despite advances in diagnosis and treatment, outcomes in low- and middle-income countries (LMICs) like Pakistan remain sub-optimal due to limited diagnostic facilities, treatment delays, and economic barriers. Objective: This study provides a comprehensive comparative analysis of OS and ES among Pakistani children, focusing on epidemiological trends, clinicopathological features, diagnostic challenges, management practices, and prognostic outcomes. Methods: This paper integrates data from peer-reviewed literature, registry reports, and regional hospital-based studies between 1995–2024. Comparative data on incidence, treatment modalities, and survival patterns were synthesized from tertiary care centers and pediatric oncology units across Pakistan. Results: Osteosarcoma accounted for approximately 55–60% of primary bone malignancies, with a mean age of 13.8 years and a male-to-female ratio of 1.8:1. Ewing sarcoma represented 25–30% of cases, predominantly affecting younger children (7–12 years). The most common site for OS was the metaphysis of long bones (femur, tibia), while ES favored diaphyseal regions and pelvic bones. Diagnostic delays averaged 3–6 months. Combined multimodal therapy improved survival, yet 5-year survival rates remained at 35–45%, significantly below global averages. Factors influencing poor outcomes included late presentation, high metastatic burden, and socioeconomic constraints. Conclusion: OS and ES in Pakistani children reflect global biological patterns but are exacerbated by diagnostic and treatment inequities. Early detection, multidisciplinary management, and national registry implementation are essential to improve pediatric oncology outcomes in Pakistan.